2016
DOI: 10.3389/fpsyg.2016.01766
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Virtual Reality for the Investigation of Awe

Abstract: The emotion of awe is characterized by the perception of vastness and a need for accommodation, which can include a positive and/or negative valence. While a number of studies have successfully manipulated this emotion, the issue of how to elicit particularly intense awe experiences in laboratory settings remains. We suggest that virtual reality (VR) is a particularly effective mood induction tool for eliciting awe. VR provides three key assets for improving awe. First, VR provides users with immersive and eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 55 publications
2
88
0
4
Order By: Relevance
“…Vastness is believed to be the key property of the stimulus capable of eliciting awe (Keltner and Haidt, 2003). Chirico et al (2016) proposed to use VR to create awe-inspiring experiences, as it is capable of producing vast stimuli, and can induce presence and enhance the ecological validity of the experience. The virtual environment should be designed to highlight the vastness of space and possibly other environments that may be included in the virtual journey to build up the sense of awe.…”
Section: Vastnessmentioning
confidence: 99%
“…Vastness is believed to be the key property of the stimulus capable of eliciting awe (Keltner and Haidt, 2003). Chirico et al (2016) proposed to use VR to create awe-inspiring experiences, as it is capable of producing vast stimuli, and can induce presence and enhance the ecological validity of the experience. The virtual environment should be designed to highlight the vastness of space and possibly other environments that may be included in the virtual journey to build up the sense of awe.…”
Section: Vastnessmentioning
confidence: 99%
“…Emotional appraisal leading to the experience of awe includes two distinctive elements, namely the feeling of vastness (perceptual or conceptual) and need for accommodation (i.e., the need for updating one's mental schemas to adapt them to the extraordinary). Recent research demonstrated that immersive technologies (e.g., Virtual Reality and 360° immersive videos) can be used to induce profound awe experiences in controlled environments, such as the lab (Gallagher et al, 2014 ; Chirico et al, 2016 , 2017 ; Gaggioli et al, 2016 ). For instance, Chirico et al ( 2017 ) were able to grasp subtle differences in the emergence of awe considering both self-reported and psychophysiological measures of this emotion.…”
mentioning
confidence: 99%
“…Still in a previous fMRI study we found that using the same stimuli the aweexperience was accompanied by decreased focus on the self and an accompanying reduced activity of the default mode network (DMN), which has been implicated in selfreferential processing and mind-wandering (van Elk, Gomez, et al, 2019). More powerful manipulations, e.g., by using immersive virtual reality (VR; see for instance: Chirico, Ferrise, Cordella, & Gaggioli, 2018;Chirico, Yaden, Riva, & Gaggioli, 2016;Reinerman-Jones, Sollins, Gallagher, & Janz, 2013) are likely to induce stronger feelings of awe, thereby enhancing the likelihood of detecting an eventual effect of awe on time perception. For instance, viewing earth from space in a virtual environmentas if floating through a space stationelicited strong feelings of awe; and immersive 3D videos of vast landscapes induced stronger feelings of awe than the 2D videos that are typically used in studies on awe (and in the present study as well).…”
Section: Discussionmentioning
confidence: 97%